Repeated misdiagnosis of squamous cell carcinoma of the thyroid: a case report - Yu, Zheng; Tingting, Ding; Jianyong, Zhang; Yunsong, Peng (Frontiers in oncology, 2025)
Squamous cell carcinoma of the thyroid (SCCT) represents a rare subtype of thyroid malignancy characterized by a poor prognosis and is frequently misdiagnosed as subacute thyroiditis (SAT). This report discusses a case of SCCT that was recurrently misdiagnosed with neck pain as the initial clinical presentation. An 80-year-old Asian female presented multiple times to the department of emergency, department of vascular and thyroid surgery, and department of endocrinology due to a painful neck mass. Ultrasonography identified a cystic solid mass in the right thyroid lobe, measuring 4.55 cm*3.2 cm. Enhanced computed tomography (CT) scanning revealed a significant enlargement of the right thyroid lobe, with an irregular mass exhibiting indistinct boundaries and blurred surrounding spaces. Laryngoscopic examination demonstrated immobilization of the right vocal cord and inadequate glottic closure. The erythrocyte sedimentation rate (ESR) was elevated to 94 mm/h. Thyroid function tests indicated subclinical thyrotoxicosis. The patient was initially diagnosed with subacute thyroiditis, and her symptoms improved following treatment with glucocorticoids and analgesics. One month following treatment, the patient experienced dyspnea, and subsequent computed tomography (CT) imaging revealed tracheal compression and narrowing, which contributed to the respiratory distress. A biopsy of the tumor was conducted, and pathological examination confirmed the presence of squamous cell carcinoma. To definitively diagnose SCCT, pathological examination and immunohistochemical analysis are required. Early and accurate diagnosis is essential for developing appropriate treatment strategies and enhancing patient survival rates. It is imperative for clinicians to comprehend this rare and life-threatening disease to enhance treatment efficacy.